Caminos para co-construir una cultura ambiental junto a un grupo de profesores de STEM del Gimnasio Vermont de Bogotá (2020)
Ecological literacy is learning about the nature and how it works, process that implies knowledge, care and practical skills within a system. Due to its importance within education in schools and universities in Colombia, it is necessary to involve it in the projects and curricula of educational institutions. In Vermont School, the STEM (Science, Technology, Engineering and Mathematics) approach has been applied in the fourth grade for the last two years. The present research sought to answer the question How to co-build an environmental culture in the Vermont School, through an attempt to articulate PRAE and STEM To achieve this joint construction, a holistic knowledge about the concept of sustainability was explored with four STEM teachers, in order to use it as the axis of the environmental culture to be co-built, and with it present design a model STEM project to work with the students. In this sense, it was proposed to use participatory action research as a strategy with teachers linked to the STEM area of the school. Data were collected through interviews, workshops, focus groups, documents, and artifacts. The results obtained reflect the objectives and guidelines on the PRAE of the Vermont School, the complexity reflected in the visions of sustainability and environmental education of the teachers, the ideas to work in projects on sustainable STEM and the ways in which this can transform the visions on society and culture that people may have. The discussion of these results points to guidelines for an environmental policy in the school that reflect the form of transmission to the students of certain values and actions, in such a way that a sustainable relationship with our environment is promoted through education.